2015
DOI: 10.4049/jimmunol.1402168
|View full text |Cite
|
Sign up to set email alerts
|

The V Gene Repertoires of Classical and Atypical Memory B Cells in Malaria-Susceptible West African Children

Abstract: Immunity to Plasmodium falciparum malaria is naturally acquired in individuals living in malaria-endemic areas of Africa. Abs play a key role in mediating this immunity, however, the acquisition of the components of Ab immunity, long-lived plasma cells and memory B cells (MBCs), is remarkably inefficient, requiring years of malaria exposure. Although long-lived classical MBCs (CD19+/CD20+/CD21+/CD27+/CD10-) are gradually acquired in response to natural infection, exposure to P. falciparum also results in a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 48 publications
6
35
0
Order By: Relevance
“…The FCRL5 2 subset proliferates more robustly than does the FCRL5 + subset in response to stimuli and expresses lower levels of inhibitory receptors. Intriguingly, we found that FCRL5 + TLM B cells from healthy adults displayed significantly lower SHM rate and shorter replication history than did classical memory B cells, similarly to what was reported in children exposed to malaria (45). However, adults exposed to malaria, who presumably encountered more rounds of malaria infection than did children, display similar SHM rates and replication histories in their TLM and classical memory B cell subsets (12,40).…”
supporting
confidence: 83%
“…The FCRL5 2 subset proliferates more robustly than does the FCRL5 + subset in response to stimuli and expresses lower levels of inhibitory receptors. Intriguingly, we found that FCRL5 + TLM B cells from healthy adults displayed significantly lower SHM rate and shorter replication history than did classical memory B cells, similarly to what was reported in children exposed to malaria (45). However, adults exposed to malaria, who presumably encountered more rounds of malaria infection than did children, display similar SHM rates and replication histories in their TLM and classical memory B cell subsets (12,40).…”
supporting
confidence: 83%
“…1), including malaria, in which V gene repertoires and parasite-specific mAbs isolated from IgG + classical memory (equivalent to RM) and atypical memory (equivalent to TLM) B cells have been described recently (56, 57). Few differences were found between the 2 B cell populations, since both contributed to protective B cell immunity; where differences were found, they functionally favored atypical memory B cells, namely, higher levels of SHM and frequencies of polyreactivity (56).…”
Section: Discussionmentioning
confidence: 99%
“…Immune repertoire next generation sequencing of the VH and VL in naïve, classical MBCs and aMBCs from malaria-exposed individuals showed no significant differences in their SHM rate (26, 30). Both populations had undergone a similar number of cell divisions, had similar clonal expansion profiles and shared approximately 10% of their VH clones.…”
Section: Introductionmentioning
confidence: 93%